he Performance of the Indonesian Press in the Era of Decentralization: Moving Beyond its Imperative Function - Abrar, Ana Nadhya (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2008)
In this study I took a normative approach to examine the performance of the Indonesian Press in the era of decentralization. My approach included intensive observations on the Indonesia press system and survey among 330 Indonesian journalists and 55 head regencies and 55 regencyâs secretaries. My analysis of the data and their context revealed the professionalism of Indonesian journalists. In their own opinion, the Indonesian journalists had a high level ofprofessionalism. However, the bureaucrats questioned their self-assurance. Therefore, it was difficult to determine the actual level of professionalism of the Indonesian Journalists throughout the many regions in Indonesia. Fortunately, the Indonesian journalists were free to report news according to the values in which theybelieved.Basedonthiscondition,theIndonesiapressownersno longer had to fulfill the political and commercial imperative functions of the press. The Indonesian press did not limit itself to report political news, but also cultural news to improve of life of Indonesian citizens. In conclusion, I consider that the Indonesian press has moved beyond its imperative function.